First indication of Storegga tsunami deposits from East Greenland: - Wagner, B.; Bennike, O.; Klug, M.; Cremer, H. (2007)
A 2.73 m long sediment sequence from Loon Lake, located at 18m a.s.l. on outer Geographical Society Ø, East Greenland, was investigated for its chronology and changes in physical and biogeochemical properties, macrofossils, and grain-size distribution. The predominance of marine fossils throughout the sequence, dated by 14C AMS to between 8630 and 7535 cal. yr BP, shows that the Loon Lake at that time was a marine basin, which according to existing sea-level curves was about 15-35 m deep. The sequence mainly consists of fine grained homogeneous sediments, which are interrupted by a 0.72 m thick sandy horizon with erosive basis and distinct fluctuations in the grain-size distribution and in the physical and biogeochemical properties. According to the radiocarbon dates, this sandy horizon was deposited after 8500-8300 cal. yr BP and is interpreted as originating from the Storegga tsunami. The record from Loon Lake provides the first indication of Storegga tsunami deposits from East Greenland. Copyright © 2006 John Wiley & Sons, Ltd.